The influence of the coaches’ demographics on young swimmers’ performance and technical determinants - Marinho, D.A. (2020)
The purpose of this study was to understand the relationship between the coaches’ demographics (academic degree and/or coaching level and/or coaching experience) and young swimmers’ performance and technical ability. The sample was composed by 151 young swimmers (75 boys and 76 girls: 13.02 1.19 years old, 49.97 8.77 kg of body mass, 1.60 0.08 m of height, 1.66 0.09 m of arm span), from seven different clubs. Seven coaches (one per club) were responsible for the training monitoring. Performance and a set of biomechanical variables related to swim technique and efficiency were assessed. The swimmers’ performance was enhanced according to the increase in the coaches’ academic degree (1: 75.51 10.02 s; 2: 74.55 9.56 s; 3: 73.62 7.64 s), coaching level (1: 76.79 11.27 s; 2: 75.06 9.31 s; 3: 73.65 8.43 s), and training experience ( 5-y training experience: 75.44 9.57 s; >5- y training experience: 74.60 9.54 s). Hierarchical linear modeling retained all coaches’ demographics characteristics as main predictors (being the academic degree the highest: estimate = -1.51, 95% confidence interval = -0.94 to -2.08, p = 0.014). Hence, it seems that an increase in the demographics of the coaches appears to provide them with a training perspective more directed to the efficiency of swimming. This also led to a higher performance enhancement